The Travels of Ibn Battuta - Hardy-Gould, Janet; Illustrated by Cuthbertson, Ollie; Series Editors: Bowler, Bill; Parminter, Sue (Oxford Oxford University Press, 2016)
'My first journey was a pilgrimage to Mecca. I got on a donkey and said Goodbye to my parents in Tangier when I was 21. My mother cried.' In this way Ibn Battuta, one of the greatest travellers in the world, begins telling his story to his nephew, Ahmed. His many journeys take him to new and interesting places far from home. He sees many strange and wonderful things, has many funny and frightening experiences, and meets many different people along the way.
Include Illustrations.
Keywords: Readers (Adult) -- Travel -- Travelers -- Voyages and travels